The Effect of Market Opportunities and Business Environment on the Income of Honey Guava Farmers in Binjai City - Asih, Surya (Universitas Negeri Medan, 2024)
The purpose of this study is to determine the effect of Market Opportunities and Environmental Conditions partially or simultaneously on the Income of Honey Guava Farmers in Binjai City. The population in this study was all Honey Guava Farmers in Binjai City using a sample of 63 people. To obtain data in the preparation of this thesis, the author uses inasutionrumen; documentation studies and interviews, as well as questionnaires. In analyzing data using multiple linear regression, t test, F test and determination test. Based on the results of the partial test (t-test), it can be concluded that Market Opportunities have a positive and significant effect on the Income of Honey Guava Farmers in Binjai City. The more often Market Opportunities are carried out, the higher the level of Income of Honey Guava Farmers in Binjai City. Environmental Conditions have a positive and significant effect on the Income of Honey Guava Farmers in Binjai City. The better the environmental conditions, the higher the income level of Guava Honey Farmers in Binjai City. Market Opportunities and Environmental Conditions together have a significant effect on the Income of Honey Guava Farmers in Binjai City. Market Opportunities and Environmental Conditions are able to explain their effect on the income of Honey Guava Farmers in Binjai City by 55.2%.